The intertropical Brazilian species of Panochthus (Xenarthra, Cingulata, Glyptodontoidea): a reappraisal of their taxonomy and phylogenetic affinities - Porpino, Kleberson de O. (2014)
Four species of Panochthus (P. greslebini, P. jaguaribensis, P. oliveira-roxoi, and P. rochai) have been described from the late Pleistocene of northeastern Brazil. P. oliveira-roxoi, and P. rochai have been considered loosely as synonyms of P. greslebini. This paper reevaluates the referred material, diagnostic characters, and validity of these species and includes a cladistic analysis of 25 caudal tube and carapace characters to determine their positioning relative to other species of Panochthus. P. greslebini and P. jaguaribensis are valid species and differ from the other species of Panochthus by unique combinations of caudal tube characters. Carapace fragments previously attributed to P. jaguaribensis are in fact fragments of cephalic shields. These fragments and the isolated ostoderms previously described for P. jaguaribensis cannot be confidently assigned to this species. We support the interpretation of P. rochai as a junior synonym of P. greslebini, but P. oliveira-roxoi is actually a nomen dubium instead of a synonym of P. greslebini. Our analysis yielded a fully resolved tree in which Panochthini, as traditionally defined, is paraphyletic and the species formerly attributed to Panochthus form a monophyletic group, echoing recent findings based on a different dataset. Within Panochthus, the Brazilian species form a clade with the Bonaerian species P. subintermedius, which is the sister species to P. greslebini. Instead of a more basal position suggested in early and recent works, P. jaguaribensis is deeply nested within the clade encompassing the species of Panochthus.